2004
DOI: 10.1163/1568530042880695
|View full text |Cite
|
Sign up to set email alerts
|

Animals, Women, and Weapons: Blurred Sexual Boundaries in the Discourse of Sport Hunting

Abstract: The furor and public outrage surrounding the release of a fictionalized video in which naked women are hunted down and shot with paintball guns ("Hunting for Bambi") inspired this paper. Arguing that distressing representations of hunting as a sexually charged activity are resilient popular culture images, this paper examines the theoretical framework that links hunting with sex and women with animals and the empirical evidence of such linkages in the hunting discourse of a popular newsstand periodical. Contem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 15 publications
(10 reference statements)
0
11
0
1
Order By: Relevance
“…The main reason for the controversy surrounding it is the fact that there is killing involved in a leisure activity, which brings into play arguments about violence, brutality, manliness and anthropocentrism, amongst others (Bergman, 2005;Cartmill, 1993;Ingold, 1994;Kalof, Fitzgerald & Baralt, 2004).…”
Section: Some Ethical Issues Related To Huntingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for the controversy surrounding it is the fact that there is killing involved in a leisure activity, which brings into play arguments about violence, brutality, manliness and anthropocentrism, amongst others (Bergman, 2005;Cartmill, 1993;Ingold, 1994;Kalof, Fitzgerald & Baralt, 2004).…”
Section: Some Ethical Issues Related To Huntingmentioning
confidence: 99%
“…According to authors such as Mallory (2001), Collard and Contrucci (1989) and Kalof, Fitzgerald and Baralt (2004), hunting perpetuates the idea of masculine dominance over all 'others', so often the analogy with sex in hunting discourse demonstrate the symbolic meanings attached to the practice (Kalof, Fitzgerald & Baralt, 2004). Masculinity, dominance and power are incessantly invoked in these discourses which, once again, would justify a special relationship existing between women and nonhuman animals -especially the ones, that is, the animals, involved in the hunting act.…”
Section: Ecofeminist's Approach To Huntingmentioning
confidence: 99%
“…Masculinity was validated through various traditions such as "shirt-tail cutting," a ritual that emphasizes the humiliation of a hunter who misses a clear shot at a deer; his shirt-tail is cut by a gang of men, leaving the shirt ineffective and symbolically castrating him, and his exposed buttocks feminize and emasculate him as a failed hunter (Bronner, 2004, 23). In another study of the contemporary hunting discourse, a widely-read hunting magazine was examined for representations of hunting as a sexually charged activity (Kalof, Fitzgerald & Baralt, 2004). The authors found evidence of the sexualization of animals, women and weapons in narratives of traditional masculinity, such as references to a victorious killing as a "score," hunting as "hot and heavy action," male animals as "hot-to-trot teenage bucks," and female animals as "coy does" (Kalof, Fitzgerald & Baralt, 2004).…”
Section: Sport Hunting: a Cultural Dialogue On Male Hunters Female Pmentioning
confidence: 99%
“…In another study of the contemporary hunting discourse, a widely-read hunting magazine was examined for representations of hunting as a sexually charged activity (Kalof, Fitzgerald & Baralt, 2004). The authors found evidence of the sexualization of animals, women and weapons in narratives of traditional masculinity, such as references to a victorious killing as a "score," hunting as "hot and heavy action," male animals as "hot-to-trot teenage bucks," and female animals as "coy does" (Kalof, Fitzgerald & Baralt, 2004).…”
Section: Sport Hunting: a Cultural Dialogue On Male Hunters Female Pmentioning
confidence: 99%
“…Les mondes païen et chrétien du Moyen Âge étaient coutumiers de ces récits mettant en jeu des êtres hybrides ainsi que des métamorphoses, passages d'un état humain à un état animal et inversement (Sax, 1998). Par ailleurs, les connotations sexuelles de la chasse mettent en évidence la virilité de cette pratique et une vision sté-réotypée de la femme (pour une analyse des conservatismes entretenus par cette pratique, voir Kalof et al, 2003Kalof et al, et 2004. On retrouve ici l'idée de catégories dominées, parmi lesquelles femmes et animaux sont placés en situation d'infériorité par rapport aux hommes chasseurs.…”
Section: La Chasseunclassified